Performativity of Gender during migration transit in De Nadie (2005) directed by Tin Dirdamal - Rodríguez, Sonia A. (2021)
During a time of global massive exodus, I explore the documentary De Nadie (2005) by Tin Dirdamal. Through a variety of narrative instances, this film presents the still very present migrant conditions and the experience of Central American individuals traversing Mexico in their journey to the United States. Considering the exclusion in the past of feminine migrant characters, contemporary cinema and literary narrative present cultural and social meanings that bring to life the presence of women as protagonists in their vertiginous border crossing, under mobility regimes. These narratives provide evidence of women’s identity transcendence beginning with their displacement. In specific, I examine De Nadie (2005) under the lense of gender performativity of the Honduran María, before and during her migratory mobilization.